Analyzing ads Under Calla in an EFL Classroom. A Case Study with Middle School Students in Colombia (2023)
The increased access to television, computers, or mobile devices means that children not only have more access to digital information, but they also need to be able to assess or filter it by themselves. The current research proposal seeks to understand how a group of middle school students used critical thinking skills while being exposed to information provided by advertisements. In this qualitative case study, five students analyzed advertisements following lessons planned under the Cognitive Academic Language Learning Approach (CALLA) model.  The instruments for data collection, such as students’ artifacts and transcripts of the workshops, were analyzed under a thematic analysis. The main findings revealed how students recalled their previous knowledge and experiences regarding TV ads to face new issues that affect their realities and social context. Similarly, the students identified hidden messages and situations in the visual content. Indeed, the CALLA model unveiled students’ critical reflections on the world today.